The multifunctional Ca2 +/calmodulin-dependent protein kinase II delta (CaMKIIδ) phosphorylates cardiac titin's spring elements - Hidalgo, Carlos G. (2013)
Titin-based passive stiffness is post-translationally regulated by several kinases that phosphorylate specific spring elements located within titin's elastic I-band region. Whether titin is phosphorylated by calcium/calmodulin dependent protein kinase II (CaMKII), an important regulator of cardiac function and disease, has not been addressed. The aim of this work was to determine whether CaMKIIδ, the predominant CaMKII isoform in the heart, phosphorylates titin, and to use phosphorylation assays and mass spectrometry to study which of titin's spring elements might be targeted by CaMKIIδ. It was found that CaMKIIδ phosphorylates titin in mouse LV skinned fibers, that the CaMKIIδ sites can be dephosphorylated by protein phosphatase 1 (PP1), and that under baseline conditions, in both intact isolated hearts and skinned myocardium, about half of the CaMKIIδ sites are phosphorylated. Mass spectrometry revealed that both the N2B and PEVK segments are targeted by CaMKIIδ at several conserved serine residues. Whether phosphorylation of titin by CaMKIIδ occurs in vivo, was tested in several conditions using back phosphorylation assays and phospho-specific antibodies to CaMKIIδ sites. Reperfusion following global ischemia increased the phosphorylation level of CaMKIIδ sites on titin and this effect was abolished by the CaMKII inhibitor KN-93. No changes in the phosphorylation level of the PEVK element were found suggesting that the increased phosphorylation level of titin in IR (ischemia reperfusion) might be due to phosphorylation of the N2B element. The findings of these studies show for the first time that titin can be phosphoryalated by CaMKIIδ, both in vitro and in vivo, and that titin's molecular spring region that determines diastolic stiffness is a target of CaMKIIδ.